The role of PAX1 methylation in predicting the pathological upgrade of cervical intraepithelial neoplasia before cold knife conization - Li, Mingzhu; Zhao, Chao; Zhao, Yun; Li, Jingran; Wang, Jingyuan; Luo, Hongxue; Tang, Zhijian; Guo, Yan; Wei, Lihui (Frontiers in Oncology, 2023)
Objective: To explore the ability of PAX1 methylation (PAX1m) to predict the pathological upgrade of cervical intraepithelial neoplasia (CIN) before cold knife conization (CKC). Methods: A total of 218 women that underwent colposcopy-directed biopsy (CDB) pathology for the confirmation of CIN2 and CIN3 between December 2020 to September 2021 were enrolled in this study. The methylation levels of PAX1 (PAX1m) were determined by quantitative methylation-specific polymerase chain reaction (qMSP). Receiver operating characteristic curve was used to identify the optimal cut-off value of PAX1m for predicting the pathological upgrade of disease. Results: In the CDB-confirmed CIN2 group, 36% of CIN2 was found to have pathologically upgraded to CIN3 and 30% regressed to low-grade squamous intraepithelial lesion (LSIL) and below, and none of CIN2 upgraded to early-stage cervical cancer (ESCC) after CKC. In the CDB-confirmed CIN3 group, 19.5% (23/118) of CDB-confirmed CIN3 were pathologically upgraded to ESCC after CKC. Regardless of CIN2 or CIN3, the PAX1m level of women with upgraded pathology after CKC was significantly higher than that of women with degraded pathology. The optimal △Cp cut-off value of PAX1m in predicting CIN3 to be upgraded to ESCC after CKC was 6.360 and the area under the curve (AUC) was 0.814, with higher sensitivity (78.3%) and specificity (84.2%) than cytology≥LSIL (Se:78.3%;Sp:58.9%) and HPV16/18 positive (Se:73.9%;Sp:46.3%) patients. Conclusions: PAX1m could be a promising auxiliary marker in predicting the pathological upgrade of CIN before CKC. We found that if the △Cp cut-off value of PAX1 methylation is lower than 6.360, it is highly suggestive of invasive cervical cancer.